INITIATION-RESPONSE-FEEDBACK (IRF) ANALYSIS IN ENGLISH CLASSROOM INTERACTION AT THE EIGHTH GRADE OF UPTD SMP NEGERI 4 MANDREHE IN 2022/2023 - Gulo, Sophyan Gusniwati; Harefa, Afore Tahir; Telaumbanua, Kristof Martin E. (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The objective of the research is find out the dominant and why do the dominant applied teacher and students in classroom interaction at the Eighth Grade of UPTD SMP Negeri 4 Mandrehe in 2022/2023. The subjects were class VIII B with 21 students and 1 English teacher. The research findings was concluded that the teacher-students of VIII-B of UPTD SMP Negeri 4 Mandrehe in English classroom interaction through IRF (Initiation-Response-Feedback) was the dominan applied in classrom interaction in initiation is convergent question there were 32 (51%). In response, it found that the dominant applied in classroom interaction in response is similar students’ response there were 41 (64%), The last is Feedback it found that the dominant applied in classroom interaction in feedback is acknowledging a correct there were 24 (62%) the teacher praises the student for a correct answer. Based on the findings, the researcher recommends that teachers should be use a variety of question, this helps to encourage students’ critical thinking and creativity. Then, teachers should give feedback to students who answer questions to show that the teacher values their participation in class interaction.